A systematic review of nonsurgical single-visit versus multiple-visit endodontic treatment - Wong AWY; Zhang C; Chu CH (Dove Medical Press, 2014)
Amy WY Wong, Chengfei Zhang, Chun-hung Chu Faculty of Dentistry, The University of Hong Kong, Hong Kong Special Administrative Region, People's Republic of China Abstract: Conventional endodontic treatment used to require multiple visits, but some clinicians have suggested that single-visit treatment is superior. Single-visit endodontic treatment and multiple-visit endodontic treatment both have their advantages and disadvantages. This paper is a literature review of the research on nonsurgical single-visit versus multiple-visit endodontic treatment. The PubMed database was searched using the keywords (endodontic treatment OR endodontic therapy OR root canal treatment OR root canal therapy) AND (single-visit OR one-visit OR 1-visit). Review papers, case reports, data studies, and irrelevant reports were excluded, and 47 papers on clinical trials were reviewed. The studies generally had small sample sizes, and the endodontic procedures varied among the studies. Meta-analysis on the selected studies was performed, and the results showed that the postoperative complications of the single-visit and multiple-visit endodontic treatment were similar. Furthermore, neither single-visit endodontic treatment nor multiple-visit treatment had superior results over the other in terms of healing or success rate. Results of limited studies on disinfection of the root canals using low-energy laser photodynamic therapy is inconclusive, and further studies are necessary to show whether laser should be used in endodontic treatment. This review also found that that neither single-visit endodontic treatment nor multiple-visit treatment could guarantee the absence of postoperative pain. Since the study design of many studies displayed significant limitation and the materials and equipment used in endodontic treatment have dramatically changed in recent years, prospective randomized clinical trials are needed to further verify the postoperative pain and success rates of single-visit versus multiple-visit endodontic treatment. Keywords: single-visit endodontics, non-surgical endodontics, systematic review, root canal therapy